Avaliação da entomofauna em frutos de espécies florestais do cerrado - Silva, Ivani Pereira da (2014)
One form of plants reproduction is accomplished through seedlings originating from seed banks, where most of these seeds may be attacked by insects, causing partial damage and even unfeasible the reprodution, justifying the research to know more about eating habits these insects species. The study aimed to determine the insect fauna that occurs in fruits of some forest species from the savannah and determine their respectives damaging in the fruit. The studies was placed in the Garden Farm, Salgadeira region , both located in the municipality of Chapada dos Guimarães, and savannah area, located in municipality of Cuiabá, all places in the State of Mato Grosso, Brazil. The collections of fruits were carried out from April to November 2013. The identification was performed by comparison with specimens from the collection of the Forest Protection Laboratory, College of Forestry Engeneering, University of Mato Grosso, and also sent to taxonomists. It was obtained 1.264 individuals, distributed in the orders Isoptera, Coleoptera, Hymenoptera, Diptera and Lepidoptera. The order with the highest number of individuals obtained was Isoptera and to forests species, Hymenaea stigonocarpa, was more infested by insects.